1968
DOI: 10.1113/jphysiol.1968.sp008612
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence of albumin and sodium transport in the foetal and new‐born pig intestine

Abstract: SUMMARY1. Everted sacs of new-born pig intestines incubated in bicarbonate saline at 370 C, transferred bovine plasma albumin across the mucosa into fluid bathing the serosa, the amount transferred increasing as the concentration of albumin in the mucosal fluid was raised from 0 5 to 16 g/100 ml.2. The rate of albumin transfer across the foetal pig intestine showed an apparent maximum, about 400,tsg/g intestine/hr, 2 weeks before birth.The transfer at birth, about 200 ,ug/g intestine/hr, fell sharply during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1971
1971
1991
1991

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Protein-dependent water and ion transport. The presence of albumin in fluid bathing the mucosal surface of everted intestinal sacs, prepared from piglets taken at birth, stimulates the transfer of both water and sodium to the serosal surface (Brown et al 1968). Results presented in Table 2 show that the net movement of potassium into the serosal solution is also stimulated when albumin is present in the mucosal solution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Protein-dependent water and ion transport. The presence of albumin in fluid bathing the mucosal surface of everted intestinal sacs, prepared from piglets taken at birth, stimulates the transfer of both water and sodium to the serosal surface (Brown et al 1968). Results presented in Table 2 show that the net movement of potassium into the serosal solution is also stimulated when albumin is present in the mucosal solution.…”
Section: Resultsmentioning
confidence: 99%
“…There remains the problem of how albumin, presented to the intestine in a high sodium, low potassium medium, can stimulate the serosal transfer of water, sodium and potassium. Previously it was shown that albumin did not change the serosal transfer of glucose (Brown et al 1968) and there is no evidence to suggest that albumin is being degraded, so one must assume that the stimulation is not connected with mucosal metabolism. Sodium probably promotes pinocytosis so that extra ions enter the mucosa, either as fluid trapped within vesicles, or because a decreased membrane resistance allows ions to diffuse more readily into the intestinal epithelium (Brandt & Freeman, 1967).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar inhibition of other transport systems has been found to take place immediately after birth at a time when this tissue is transporting macromolecules (Brown, Smith & Witty, 1968 (Smith, 1984).…”
Section: Resultsmentioning
confidence: 90%
“…There is in addition some evidence to suggest a direct interaction between the transport of sodium and protein in the pig intestine. The immediate effect of protein is to increase the net absorption of sodium in unsuckled animals (Smith, 1971) whereas the continued ingestion of colostrum inhibits sodium transport (Brown, Smith & Witty, 1968). The present work attempts to characterize different mechanisms for sodium transport in the piglet intestine, examines in greater detail the possible ways in which protein transport might interact with that for sodium and compares this with what is known concerning the mechanism of sodium transport in other mammalian intestines.…”
Section: Introductionmentioning
confidence: 96%